Birth-and-Death-Based Multipath Cluster Channel Model for Massive MIMO. Issue 1 (1st February 2022) - Lu, Yanping; Liu, Liu; Liu, Kai
Abstract: In this paper the propagation characteristics of large-scale multi-antenna communication system are investigated. we give an insight into sub-channel correlation, and from which the non-stationary characteristics are deduced. Some in-field channel sounding are carried out with interesting frequencies of 1.4725GHz and 4.5GHz. Regarding to the channel measurements and data analysis we take an educated guess, and construct a birth-and-death-based Markov Model to characterize the multipath cluster's evolution over the array, which explained the micro-changes of the radiation propagation environment. And the model is found to be highly coincide with propagation theory.